Treatment of Trans-Sphincteric Fistula-In-Ano with Combined Therapy of Laser and Kshara Sutra - Mohammad Amir,; Mrigank Shekhar,; Arun Kumar Singh,; Neelam Gupta, (International Journal of Ayurveda and Pharma Research, 2022)
Fistula-in-ano is most infectious disease among all the ano-rectal disorders since ancient times. Over the past few decades, various techniques are being evaluated in terms to prevent its recurrence and complications; it is still a challenging surgical disease. The sign and symptoms of fistula in ano resembles with Bhagandar described in Ayurvedic classics. Kshara sutra therapy (medicated thread) practiced in Ayurveda Since ancient time for the management of Naadi Vrana and Bhagandar. Kshara sutra therapy has revolutionized the treatment of fistula-in-ano, as it treat the main culprit of fistula that is cryptoglandular origin but the drawback of Kshara sutra therapy are as it takes more number of hospital visit, long anxiety period and discomfort. In present time LASER therapy is used in various medical surgery and also in proctology like in fistula as FILAC, DLPL etc. Diode LASER 980nm (Radial Fibre) burns unhealthy granulation tissues in 360° manner with less or minimal pain, LASER act as photo evaporation effect and leads to the shrinkage of the fistula tract. But if we do LASER in internal opening of fistula it provides a bare area for microbes and creates a chance to re-infects the crypts and anal glands, which further leads recurrent fistula formation. Therefore a novel technique for sphincter preserving surgery proposed as combined therapy of Kshara sutra ligation for main culprit that is cryptoglandular infection as SMAK (Sub Mucosal Application of Kshara Sutra) and LASER, shrink the remaining fistula tract instantly